Development of a multiplex bead assay to detect exposures to tick-borne diseases in dogs and a comparative performance analysis - Black, Kelley Elizabeth (Kansas State University, 2016)
Tick-borne bacteria, Ehrlichia canis, Anaplasma platys, and Ehrlichia chaffeensis are significant zoonotic pathogens of dogs and humans worldwide. In tropical regions such as Grenada, West Indies, dogs represent a major reservoir for E. canis and A. platys, and they are often co-infected. The purpose of this study was to develop a serologic, multiplex bead-based assay to detect species-specific exposures to E. canis, A. platys, and E. chaffeensis in dogs for purposes of surveillance and public health. Peptides from specific outer membrane proteins of P30 for E. canis, OMP1X of A. platys, and P28-19/P28-14 of E. chaffeensis were coupled to magnetic beads and assays were optimized using the multiplex Luminex xMAP® platform. In experimentally infected dogs, the multiplex assay successfully detected antibodies for E. canis and E. chaffeensis, but not A. platys. In the Grenadian population (n=104), the multiplex assay and the in-house ELISA, the SNAP® 4Dx®, detected A. platys antibodies as well as Ehrlichia spp.. Multiplex assay results were found to have “good” and “very good” agreement with the ELISA and IFA for E. canis antibody-positive dogs (K value of 0.73 and 0.84 respectively), while ELISA and IFA had “very good” agreement with each other (K value of 0.85). A. platys multiplex results had only “poor” agreement with ELISA and IFA (K value of -0.02 and 0.01, respectively), while the ELISA and IFA tests had “moderate” agreement with each other (K value of 0.5). These tests showed the prevalence of exposure to E. canis to be comparable with previous studies (38% in 2014), but a doubling of exposure to A. platys determined by IFA and 4Dx® from 9% in 2006, to 20% in 2014. Bayesian modeling (performed on E. canis data only) suggested conditional independence between the IFA, 4Dx®, and MAG tests using consensus priors calculated from literature, and that the bead-assay had comparable sensitivity and specificity to the IFA and ELISA tests. In conclusion, the multiplex peptide assay performed well in detecting the seropositive status of dogs to E. canis and had good agreement with commercial assays; however, more work needs to be done to assess performance in populations of dogs with exposures to multiple species of Ehrlichia. Further, the reasons for low seroreactivity to A. platys need to be further investigated.
Keywords: Ehrlichia; Anaplasma; Bayesian; bead assay; diagnostic test